On the streets and on the road: identity in transit in TurkishGerman travelogues on screen - Burns, Rob (New Cinemas: Journal of Contemporary Film, 2009)
As with the iconography of exilic and diasporic cinema generally, the TurkishGerman cinema of the 1970s and 1980s featured images of captivity and claustrophobic spaces. More recently, in tandem with a shift away from the tendency to represent the migrant as victim, this cinema has portrayed its protagonists as on the move, either within urban environments or in transit between Turkey and Germany. Focusing primarily on this last category of film, the article will examine the significance attaching to such transnational journeys. In some cases they serve mainly as a means of narrative closure in the form of enforced (or even self-imposed) deportation; while in genuine road movies the journey from Turkey to Germany may be represented in miserabilist terms as one of pain and despair or more positively as one of quest and self-assertion. In Fatih Akin's films, particularly In July, Head-On and The Edge of Heaven , where the protagonists journey in the reverse direction (from Germany to Turkey), transnational travel entails a quest either for redemption or for new forms of identity.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9uY2luLjcuMS4xMV8x